Head injury assessment in the elite level rugby union in Japan: Review of 3 seasons - Tajima, T.; Ota, O.; Nagayama, M.; Takahashi, M.; Yamada, M.; Ishiyama, N.; Yoshida, I.; Takemura, M.; Hara, K.; Akama, T.; Mitsumori, N.; Higashihara, J.; et al. (International Journal of Sports Medicine, 2022)
Head Injury Assessment (HIA) is the screening tool for head injury during a rugby game. The purpose of this study was to investigate the epidemiology of HIA in the Japan Rugby Top League (JRTL). The incidences of HIA, defined concussion (per 1,000 player-hours) and repeated concussions were evaluated in three seasons (2016-17, 2017-18, 2018-19; total 360 games). The HIA incidence rates were 12.7 (95% confidence interval 9.5-15.9), 20.8 (16.8-24.9), and 25.0 (20.5-29.5) in each season. HIA-1 criteria 2, which is applied for suspected concussion cases, was performed for 46 cases in the 2016-17 season, 81 cases in the 2017-18 season, and 88 cases in the 2018-19 season. The concussion incidence rates were significantly greater in the 2017-18 season (9.6/1000 player-hours, 95% confidence interval 6.8-12.4) and the 2018-19 season (14.4, 11-17.8) compared to the 2016-17 season (4.8, 2.8-6.8). The number of repeated concussion cases in the same season was 1 in the 2016-17 season and 4 in both the 2017-18 and 2018-19 seasons. This study confirmed significantly higher HIA and concussion incidence rates over time. Although the HIA system might have been established in the three seasons in JRTL, comprehensive management needs to be improved to prevent repeated concussions.